Enzymatic hydrolysis of steam pretreated bagasse : Enzyme preparations for efficient cellulose conversion and evaluation of physiochemical changes during hydrolysis - Wallace, Joshua (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScEng)--Stellenbosch University, 2013.